Effects of probiotics on neurocognitive outcomes in infants and young children: a meta-analysis - Lin, Feng-Li; Chen, Chia-Min; Sun, Cheuk-Kwan; Cheng, Yu-Shian; Tzang, Ruu-Fen; Chiu, Hsien-Jane; Wang, Ming-Yu; Cheng, Ying-Chih; Hung, Kuo-Chuan (Frontiers in Public Health, 2023)
Background Therapeutic efficacies of probiotics in improving neurocognitive functions in infants and young children remained unclear. This meta-analysis focused on different cognitive outcomes in this population. Methods Major databases were searched electronically from inception to October 2023 to identify randomized controlled trials (RCTs) that investigated the therapeutic efficacy of probiotics in enhancing cognitive functions assessed by standardized tasks. The overall effect size was calculated as standardized mean difference (SMD) based on a random effects model. Results Nine RCTs with 3,026 participants were identified. Both our primary and secondary results demonstrated no significant difference in neurocognitive outcomes between infants/children treated with probiotics and those receiving placebos. However, our subgroup analysis of studies that offered a probiotics treatment course of over six months demonstrated a significantly better neurocognitive outcome than placebos (SMD = 0.21, p = 0.03, two studies with 451 participants), but this finding was based on only two RCTs. Conclusion Despite lack of significant therapeutic effects of probiotics on neurocognitive outcomes, our finding of a positive impact of probiotics on neurocognitive development in those undergoing treatment for over six months may provide an important direction for further investigations into the enhancement of therapeutic effects of probiotics on neurocognitive development in infants and young children. Systematic review registration PROSPERO CRD42023463412.